Treatment of cystic swelling of scrotum: a clinical analysis - Charpot, Rahul; Modi, Kunal (International Surgery Journal, 2022)
Background: Cystic swellings of scrotum are usually painless and can attain a very big size without causing much discomfort. Management of cystic swelling of a particular type can be done in various ways; hence there is a necessity to study the ideal modality of management for each type of cystic swelling of scrotum possible in our setup of rural hospital. Methods: A total of 100 cases of cystic swellings of scrotum fulfilling the methodology criteria’s were subjected to preformatted study. Final diagnosis was made with clinical examination and ultrasonography of scrotum. All cases were treated surgically. Results: Most of the patients were in age group of 51-60 years (30%), presenting feature being scrotal swelling as a main complaint in 86% of cases, majority of them were right sided (60%), primary vaginal hydrocele was the commonest cystic swelling (76%), followed by epididymal cyst, spermatocele, sebaceous cyst. Lord’s plication was the procedure, which was associated with early discharge of the patient and least post-operative complications. Conclusions: Primary vaginal hydrocoele was the commonest cystic swellings of scrotum. Most of the cystic swellings were treated surgically with good results. Lord’s procedure was the least to have post-operative complication.